How to edit your name on your ORCID record. - Open Researcher and Contributor ID (ORCID) (My University, 2021)
Find out how and why to edit your name on your ORCID record.
First name (required): Your given name, or the name you most commonly go by. If you have only one name you should record it in the First Name field. If you are more widely known by your middle name, record your middle name in this name field; and if you always use both your first and middle names together, record both in this field. “First name” is the only required field, as ORCID is a global service and supports all naming conventions including those without a last or family name. This field is limited to 150 characters.
Last name: Your family name, surname, or last name. This field is limited to 150 characters.
Published name: How you prefer your name to appear when credited. This is the name that appears at the top of your ORCID record. If you want to use an initial or second family name, include it in the "Published name" field.
Also known as / other names: Additional names you may be known by. This can include an abbreviated first name, variants including middle name(s), former or alternate name(s), or name(s) in a different character set. Add each name as a single item. You can add as many other names as needed. You can change the order of display using the up and down buttons, and set the visibility of each individual name. Trusted organizations and trusted individuals can also add also known as names, and update names that they have added, if you grant them permission to add biographical information.
Keywords: ORCID